The Effect of Social Support on Job Satisfaction and Organizational Citizenship Behavior as Mediation - Sogirin; Adolf Bastian (Yayasan Education Al Aqsho Modern, 2022)
This study aims to analyze the effect of social support on organizational citizenship behavior and job satisfaction as intervening variables. The sampling technique used the PLS Equational Modeling (SEM) method. The sample was taken as many as 109 employees of the Tambusai Public Health Center and the upstream Health Center of Rokan Hulu Regency, with the research instrument being a questionnaire. The effect of social support on job satisfaction of the Rokan Hulu district health center. Based on the results of data analysis, the research hypothesis which states that there is a positive relationship between social support and job satisfaction for company employees can be accepted. This means that by looking at the existence of social support, it can be predicted how job satisfaction at the Tambusai Health Center and the Kecepatan Hulu Health Center in Rokan Hulu Regency will be. This shows that the higher the social support, the higher the job satisfaction.